The Referent of 'Our Shield' in Psalm 84,10 - Kim, Yoo-Ki (2017)
The expression 'our shield' in Ps 84,10 offers two possibilities of interpretation: taking the noun phrase as a vocative referring to the deity, or as an object of the imperative verb referring to a human king. The parallel structure of the two couplets that constitute the prayer in vv. 9-10 as well as syntactic, semantic, and pragmatic features argue in favor of taking 'our shield' as a reference to God. By calling God 'our shield', the poet prays for God’s powerful protection of the leader of the community, who is probably the poet himself.
Keywords: Bibel; Militär; Bible. Psalms 73-89; Hebrew language -- Syntax; Hebrew language -- Terms -- Magen; Peer reviewed